Checkpoint inhibitors in head and neck cancer: current knowledge and perspectives. (25th June 2018) - Samra, Bachar; Tam, Eric; Baseri, Babak; Shapira, Iuliana
Abstract : The emergence of immunotherapy has provided significant clinical improvements in the treatment of metastatic solid tumors. Recurrent/metastatic head and neck squamous cell carcinoma (HNSCC) has dismal prognosis with median survival ranging between 6and12 months. Our aim is to review the current knowledge on the role of the immune system and immune checkpoint inhibitors in HNSCC. We will focus on the landmark trials that led to the regulatory approvals of pembrolizumab and nivolumab, and discuss a few promising contenders in clinical development and highlight the need to identify better biomarkers other than programmed death-ligand 1 to improve patient selection and help predict response.